„Àwwer selbsch ém dood züèm drutz“ - Helmut Pillau (Recherches Germaniques)
One could speak of an archaeology of the living that Claude Vigée undertakes in this poem and his work as a whole. He attempts, with both vehemence and tender empathy, to reanimate the vitality that is buried beneath the systematic organization of human life. Characteristic of the Alsatian-Jewish poet is his simultaneous consideration of these paradoxes of civilizational development alongside the life situation of his Alsatian compatriots and the precarious existence of the Jews. He refuses to accept how the certainty of death dominates over the certainty of life. To acknowledge the end of living beings can signify a desire to want to block their unwelcome future. The mastery over the living, which has led to the successes of Western civilization, is based on a secret alliance with death.